Evaluation of flow of chorioretinal capillaries in healthy black and white subjects using optical coherence tomography angiography - Nathalie Massamba (Nature Portfolio, 2021)
Abstract This study compared macular capillary parameters between healthy black and white subjects using optical coherence tomography angiography (OCTA). We measured vessel density (VD) of superficial (SCP), intermediate (ICP), and deep (DCP) capillary plexuses and choriocapillaris blood flow area (BFA) of the fovea, parafovea and total 3 mm-diameter circular area centered on the fovea, as well as the foveal avascular zone (FAZ) parameters, controlling for axial length. Black subjects had lower foveal and parafoveal VD in the SCP (p = 0.043 and p = 0.014) and the ICP (p = 0.014 and p = 0.002). In the DCP, black subjects had a trend toward lower foveal and parafoveal VD. Black subjects had decreased choriocapillaris BFA in the total 3 mm area (p = 0.011) and the parafovea (p = 0.033), larger FAZ area (p = 0.006) and perimeter (p = 0.014), and a higher capillary density in a 300 μm wide region around the FAZ (FD-300) (p = 0.001). There was no significant difference in FAZ acircularity index. To our knowledge, this is the first report analyzing the three distinct retinal capillary plexuses and identifying differing baseline VD, choriocapillaris and FAZ parameters in healthy young black compared to white subjects. Larger studies are needed to validate these findings and better understand racial differences in vulnerability to ocular diseases.